Characterization of the care assistance after the implementation of the embracement, evaluation and classification of risk in a public hospital - Angela Rossaneis, Mariana (2011)
The study aimed to describe the implementation of embracement with an evaluation and classification of risk (EECR) in a public hospital of medium complexity and characterize the attendance after the implementation of this strategy. This is an exploratory descriptive study developed into two stages: at the first, the EECR implementation strategies were described, at the second, the amount of medical consultations were numbered during the period of four months after implantation and compared with the months that preceded them. The multi professional group structuring and the construction of the situational strategic planning provided the process operationalization. After implementation of EECR, 36% of users were assessed by the nurse and referred to other services, which resulted in 69% of reduction in medical care. The EECR streamlined the care of patients who required immediate treatment, considering the health risk and the suffering degree. Descriptors: User Embracement; Humanization of Assistance; Emergency Service, Hospital; Nursing Service, Hospital.